2019
DOI: 10.1186/s41938-019-0165-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of potato systemic resistance against the potato virus Y (PVYNTN), using crude filtrates of Streptomyces spp. under greenhouse conditions

Abstract: The potato virus Y (PVY) is considered one of the most important viruses in terms of both economical and biological impact. Potential of using three different Streptomyces spp. crude filtrates (SCF) to induce of resistance against tuber necrotic strain of potato virus Y (PVY NTN) in four potato cultivars namely, Spunta, Nicola, Selatar, and Diamant, were evaluated. Foliar spraying of Streptomyces netropsis DSM 40093 (SCF7), S. ambofaciens (SCF11) and S. actuosus (SCF20), applied separately on potato cultivated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…In this context, the foliar application of Streptomyces spp. CF exhibited a significant reduction of PVY in potato 39 . Thus, POT1 activates induced systemic resistance (ISR) of potato plants against AMV infection.…”
Section: Discussionmentioning
confidence: 94%
“…In this context, the foliar application of Streptomyces spp. CF exhibited a significant reduction of PVY in potato 39 . Thus, POT1 activates induced systemic resistance (ISR) of potato plants against AMV infection.…”
Section: Discussionmentioning
confidence: 94%
“…They can directly trigger or produce elicitors that can induce systemic resistance in the plant against pathogens ( Dias et al, 2017 ; Abbasi et al, 2019 ; Vergnes et al, 2020 ). Nasr-Eldin et al (2019) reported that the foliar spraying of the fermentation filtrates of Streptomyces spp. showed effective protection against potato-virus Y in all potato cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Such final fermentation products, which resulted after medium optimization and fermentation process parameters (pH, temperature, air supply and agitation) are rich in biomass and high spore numbers, but also in metabolites important for plant growth and health and can be applied directly with double effect on plants. In recent years, cell-free fermentation liquids with strong phyto-stimulating and biocontrol properties are attracting a growing interest because their action does not depend on the soil micro-and macro-biota and the typical stress factors affecting living-cell biofertilizers [10,[47][48][49][50][51]. Optimization of the fermentation medium may include introduction of additional components in order to increase the system productivity or control metabolite activity.…”
Section: Single Batch Operationsmentioning
confidence: 99%